Ultrasonic-Assisted Synthesis of Zinc Borates: Effect of Boron Sources - Dumanli, Fatma Tugce Senberber; Kipcak, Azmi Seyhun; Vardar, Duygu Sena; Tugrul, Nurcan (CHEM SOC PAKISTAN, 2020)
Sonochemistry meaning ultrasound-assisted chemistry plays an important role in the synthesis of inorganic compounds. Among these inorganic compounds, zinc borates are used for the flame-retarding agent. In this study using zinc chloride (ZnCl2), boric acid (H3BO3), Na2B4O7 center dot 10H(2)O, Na2B4O7 center dot 5H(2)O and NaOH as raw materials, a zinc borate compound in the formulae of Zn3B6O12 center dot 3.5H(2)O was obtained using an ultrasonic probe. Crystal structures of samples were identified using X-ray diffraction (XRD). The symmetric and asymmetric stretching between boron and oxygen atoms were searched by Fourier-transform infrared (FT-IR) and Raman spectroscopies. The effects of boron sources on sample morphology were examined by scanning electron microscopy (SEM). From the results, it was seen that Zn3B6O12 center dot 3.5H(2)O can easily be produced from these raw materials with the synthesis parameters of 80-90 degrees C and 40-55 min. From the SEM results, it was seen that the minimum particle size obtained was 172 nm. Reaction efficiencies were calculated between 79.6 and 94.0 +/- 0.5%. Thermal feature of the obtained pure phase, investigated with the thermogravimetric analyses. The dehydration of the synthesized Zn3B6O12 center dot 3.5H(2)O was seen between 262 and 413 degrees C with a total mass loss of 13.25%.
Keywords: Zinc borate; Sonochemistry; X-Ray diffraction; Spectroscopy; Reaction yields; FT-IR; X-RAY; Chemistry